Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report, 2020)
This paper on Bosnia and Herzegovina presents the report on the government finance statistics technical assistance mission in Bosnia and Herzegovina. Further on developing reconciliation processes, the mission provisionally finalized research to establish reconciliation procedures, without fully eliminating statistical discrepancies. On the compiling of nonbudgetary public sector units, the mission continued the development of compilation processes as started during the May 2018 mission. Considering the differences in outcomes on balance sheet transactions between the 'old' and the 'new' compilation process, further research is required to test the plausibility of these compilation processes and outcomes. The mission will liaise with IMF's European Department on an appropriate implementation procedure in coordination with other reporting units in Bosnia and Herzegovina that are also revising fiscal surveillance to the Government Finance Statistics Manual 2014 framework. The mission succeeded in resolving statistical discrepancies-at least from accounting technical point of view.